Trustees as servant-leaders: A report and reference guide - Spears, Larry (International journal of value-based management, 1993)
How have the servant-leader writings of Robert Greenleaf impacted upon society during the past twenty years? What influence has Greenleaf had upon trustees and others? And, what are people sayingtoday about servant-leadership?, While this paper seeks to provide a partial answer to these questions, its intent is to serve as an informative report on the ever-widening influence of the servant-as-leader idea—and as a resource guide for others who may wish to delve more deeply into the notion of trustees as servant-leaders., In 1974, Robert Greenleaf publishedTrustees as Servants, in which he expressed his own thoughts concerning the special role which trustees can and should play within an institution—but usually don't. His delineation of some of the barriers and solutions to effective trusteeship has since been read by over 400,000 people and has come to represent a core element of what is now generally called “trustee education.”, The central definition of servant-leadership, as defined by Greenleaf inThe Servant as Leader, is as follows: It begins with the natural feeling that one wants to serve, to serve first. Then conscious choice brings one to aspire to lead. The difference manifests itself in the care taken by the servant—first to make sure that other people's highest priority needs are being served. The best test, and difficult to administer, is: do those served grow as persons; do they while being served, become healthier, wiser, freer, more autonomous, more likely themselves to become servants? And, what is the effect on the least privileged in society; will they benefit, or at least, not be further deprived?, The past two decades have witnessed the publication of a growing number of books and articles concerning servant-leadership and its applications in a number of key areas. This now includes its uses as: a working philosophy and model in both for-profit and not-for-profit institutions; the bringing together of servant-leadership and experiential education in the related area of “service-learning”; the use of servant-leadership within community leadership programs; its use in both formal management/leadership courses and by independent consultants working directly with institutions; as a core idea for several diverse areas of personal growth and personal transformation; and as the values base for trustee education., The attached bibliographies-in-progress are intended to provide suggested readings for those who are interested in finding out more about the role of trustees as servant-leaders.